THE DIFFERENT LEADERSHIP STYLES AND THEIR IMPACT ON PROFITABILITY: A CASE STUDY OF WOMEN ENTREPRENEURS IN NORTHERN DISTRICT - Pushpanathan, A.; Ramesh, S.; Nimalathasan, B. (My University, 2013)
Leadership has been viewed from multiple perspectives like leaders’ personal characteristics, the nature of the organizational context and characteristics of subordinates. The behaviors are generic ones applicable to all types of leaders and organization and they may interactions with subordinates. Women are engaged in business for income generation for their livelihood. Especially in Northern Districts (i.e., Vavuniya; Killinochchi and Mullaitivu Districts) most of the women are engaged in small, micro and cottage industries after completing the civil war for running their families. The present study explores the women leadership styles in Northern Districts. The objective of this study is to analysis the leadership styles of Women Entrepreneurs such as Task, Relationship and leadership styles which are highly influence on their businesses. The data were collected from the women entrepreneurs in the respective districts using judgmental sampling. Exploratory factor analysis using “Varimax Rotated Factor Analysis Methods” has been used to analysis the data. The results revealed that five factors (Give responsibility to employees, Special care to job, Laid down rules only, Maintain good performance, and detail procedure) are extracted from the analysis of Task leadership styles. Four factors (Personal loyalty, Career problems, Informal relationship, and Progress of subordinates) are extracted from the analysis of Relationship leadership, and also four factors Free with subordinates, Strongly likes and dislikes, Appreciation, and Direct support) are extracted from the Participative Leadership. Finally, the regression analysis indicated that Task Leadership has negative significant relationship with profitability, and insignificant effect was observed among the relationship leadership, and participative leadership, and profitability of the organization.
Keywords: Leadership Styles; Women Entrepreneurs; Profitability